Experimental study on the effects of massive bowel resection on liver function and hepatocyte apoptosis - Bostanoğlu, Akın; Oruğ, Taner; Yıldız, Barış Doğu; Işık, Sevil; Zengin, Neslihan İnci; Evren, Ebru; Saydam, Gül Sevim (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The effects of short-bowel syndrome on liver function and liver morphology independent of parenteral nutrition have not been thoroughly investigated. Our aim was to investigate the effects of massive bowel resection on hepatocyte apoptosis and liver function in rats. Materials and Methods: A total of 37 female Sprague-Dawley rats were randomly assigned to five groups: Control (no procedure); Sham 1 [laparotomy (LT)/enterotomy (ET); evaluated on postoperative day (POD) 1]; Sham 2 (LT/ET; evaluated on POD7; Group 1 (80% bowel resection after LT/ET; POD1); and Group 2 (80% bowel resection; POD7). Blood samples were obtained for measuring aspartate aminotransferase, alanine aminotransferase, and lactate dehydrogenase levels. For assessing hepatocyte apoptosis, liver tissue samples from the median lobe were obtained and used for a terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick-end labeling assay. Results: Aspartate aminotransferase, alanine aminotransferase, and lactate dehydrogenase levels showed statistically significant differences among the five groups. Apoptotic hepatocyte counts there were statistically significant differences among groups for counts made in 20 consecutive high-power fields. However, liver sinusoidal cell apoptosis rates among groups showed statistically significant differences for counts made in 20 consecutive high-power fields, particularly on POD7 in rats undergoing massive bowel resection. Conclusion: Parenteral nutrition is not the only factor involved in liver dysfunction after massive bowel resection. Massive bowel resection alone can cause liver abnormalities. Rats undergoing massive small intestinal resection show significant temporal increases in liver sinusoidal cell apoptosis rates.